ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN PRODUK INDOSAT PADA PT X - Rika Sylvia; Diana Hayati (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
The purpose of this research is to find a marketing strategy for Indosat products that will be developed by PT X. The type of research used is descriptive qualitative with the research subjects in this study totaling 7 respondents. The data analysis technique used is SWOT analysis, namely by describing the internal environment and external environment which are the strengths, weaknesses, opportunities and threats at PT X. Based on the results of research from the internal side, PT X's strengths are greater than its weaknesses, namely the results of the IFAS calculation point is 3.51 with the difference between strengths and weaknesses having a positive value of 0.115. While from the external side the opportunities are smaller than the threats, namely the results of the EFAS calculation the point is 3.15 with the difference between opportunities and threats having a negative value of -0.105. The results of the SWOT calculation show that PT X is in quadrant II, which indicates that facing various threats, this company still has internal strength. The strategy that must be implemented is to use strength to take advantage of long-term opportunities by means of a product diversification strategy.